Ghosts I Have Been - Richard Peck (Puffin Books, 2001)
Blossom Culp is the outspoken outcast of Bluff City, always getting into trouble. No one wants to cross her, especially now that she's revealed that she can see the Unseen. Then Blossom herself is stunned, because her lie turns out to be truth. She actually does have second sight...and she is "on board" the sinking Titanic.
Keywords: Mystery -- Mystery